Kinetics and thermodynamics of densification and grain growth: Insights from lanthanum doped zirconia. (15th May 2018) - Li, Hui; Dey, Sanchita; Castro, Ricardo H.R.
Abstract: The effect of dopants (or additives) on sintering is typically addressed from a mechanistic and diffusivity perspective by focusing on how dopants affect those parameters. However, a comprehensive description of sintering needs to address the role of dopants in the thermodynamics of the system, which affects local chemical potentials driving forces and is, therefore, ultimately linked to the mass transport mechanisms themselves by the thermodynamic extremal principle. In this work, Lanthanum doped Yttria-Stabilized-Zirconia (YSZ) sintering was studied from both kinetics and thermodynamic perspectives to demonstrate the need for those complementary analyses to allow proper processing control. La caused inhibition of both grain growth and densification, which was a result of a change of interfacial energies linked to La segregation as well as of the codependence of coarsening and densification on the grain boundary energy. While La caused a modest decrease in the activation energy for densification, surface and grain boundary energies decreased from 0.95 to 0.70 J/m 2, respectively, for YSZ, to 0.80 and 0.41 J/m 2 for 2 mol% La-YSZ, indicating an increase in sintering stress. The apparent contradiction between the thermodynamic data and the observed densification trend is attributed to the reduced grain growth that trapped the system in a metastable configuration. Graphical abstract: Image 1